2023
DOI: 10.1037/dev0001487
|View full text |Cite
|
Sign up to set email alerts
|

Sleep electroencephalogram (EEG) oscillations and associated memory processing during childhood and early adolescence.

Abstract: The architecture of sleep undergoes distinct changes during childhood and early adolescence. Slow wave sleep is involved in memory processing and may support active consolidation of newly encoded representations to support the formation of abstracted “gist” memories. Here, we examined sleep and overnight memory formation in German school children (n = 33) between 7 and 15 years of age, after the encoding phase of a verbal Deese-Roediger-McDermott (DRM) task. Effects of age were analyzed on sleep electroencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…In early childhood (~5-6 years old), the timing of SO-spindle coupling is less consistent than in adulthood [85]. Coupling consistency increases as children enter adolescence, with 14-18-year olds showing more consistent coupling than 5-11-year olds [86,87]. Using a powerful longitudinal design, Hahn and colleagues showed that increases in the consistency of SO-spindle coupling across adolescence are associated with a stronger benefit of sleep for memory consolidation [58].…”
Section: Changes In So-spindle Coupling and Memory Consolidation Acro...mentioning
confidence: 99%
“…In early childhood (~5-6 years old), the timing of SO-spindle coupling is less consistent than in adulthood [85]. Coupling consistency increases as children enter adolescence, with 14-18-year olds showing more consistent coupling than 5-11-year olds [86,87]. Using a powerful longitudinal design, Hahn and colleagues showed that increases in the consistency of SO-spindle coupling across adolescence are associated with a stronger benefit of sleep for memory consolidation [58].…”
Section: Changes In So-spindle Coupling and Memory Consolidation Acro...mentioning
confidence: 99%